The Camel Adaptive Immune Receptors Repertoire as a Singular Example of Structural and Functional Genomics - Ciccarese, Salvatrice; Burger, Pamela A.; Ciani, Elena; Castelli, Vito; Linguiti, Giovanna; Plasil, Martin; Massari, Serafina; Horin, Petr; Antonacci, Rachele (Frontiers in Genetics, 2019)
The adaptive immune receptors repertoire is highly plastic, with its ability to create antigen-binding molecules and select those, which bind with high affinity to their cognate antigen to remove evading pathogens. Species have developed diverse genetic and structural strategies to create their respective repertoires. Camelids, until now considered as a case of evolutionary innovation because of their single-domain heavy-chain antibodies, represent a new mammalian model particularly useful for understanding the role of diversity in the immune system function. Here we review the current status of the camel adaptive immune receptors repertoire: i) Immunoglobulins: genomic organization, structural and functional characteristics, applications in biotechnology; ii) T-cell receptor genomic organization and functional characteristics; iii) Somatic hypermutation (SHM); iv) Major histocompatibility complex (MHC) genomic organization and diversity. (i) In camelids adaptive immune response, the antigen-binding fragment of a classical antibody is reduced to a single variable domain of the heavy (H)-chain (VHH), also referred to as Nanobody®. Nanobody-based cancer therapy revealed beneficial biophysical and pharmacological properties for in vivo applications, with indications for a low response from the immune system. (ii) In Camelus genus, the general structural organization of the TR β-locus is similar to that of the other artiodactyl species, with a pool of TRBV genes positioned at the 5’-end of three in tandem D-J-C clusters, followed by a single TRBV gene with an inverted transcriptional orientation located at the 3’-end. The evolution of the dromedary TR γ/δ loci has been favored by mutation in the productively rearranged γ/δ genes, increasing the intrinsic structural stability in the γ/δ heterodimer and influencing the affinity maturation to a given antigen similar to immunoglobulin genes. (iii) The SHMin dromedary γ/δ rearranged genes increases the repertoire diversity. Differently from γ/δ, the repertoire of β-chain is not shaped by the somatic mutation and appears reduced in size and gene content. (iv) The MHC is located on chromosome 20 in Camelus dromedarius. Cytogenetic and comparative whole genome analyses revealed the order of the three major sub-regions “Centromere-ClassII-ClassIII-ClassI”. Unexpectedly low extent of polymorphisms and haplotypes was observed in all Old World camels despite different geographic origins.